Reinforcement influence on non-autoclave foam cement concrete strength characteristics/Armavimo įtaka putų cementbetonio stiprumo charakteristikoms - Sinica, Marijonas; Dudik, Antanas; Laukaitis, Alexander; Sezeman, Georgij (Journal of Civil Engineering and Management, 2000)
The volume and surface reinforcement treatment influence on 900–1000 kg/m3 density non-autoclave foam cement concrete strength characteristics are discussed in this paper. Carbon fibres of a length up to 5 mm and diameter of 4, 6-7.7 mkm were used for volume reinforcement. An alkali- resistant glass fabric net with a 4,5 or 9 mm mesh satisfying the requirements of Austrian standard SSA-5433 was used for surface reinforcement. The chemical composition of raw materials used are given in Table 1. One glass fabric net was put on the form bottom before pouring the mixture, while the other net was put on top, pushed into the formation mixture and trowelled with a roller. The material contracts when the Portland cement hardens and microcracks appear. These microcracks have a negative influence on the materials structure, it decreases the materials strength characteristics, frost-resistance and durability. Small amounts of synthetic carbon fibres (0.2–0.4% based on solids) increase the 900 kg/m3 density foam cement concrete flexural strength from 6 to 24.5% (Fig 2). The carbon fibre adhesion to foam cement concrete is insufficient. The fibres are dragged out of the material during bending or extension (Fig 3). Besides volume reinforcement, surface reinforcement was tested by introducing a glass fabric net 2 mm below the formation mixtures surface. All the specimens were additionally reinforced with 0,2% carbon fibre. The obtained results show that samples reinforced with a 4.5 mesh net have a twice better flexural resistance than control samples. Samples reinforced with a 9 mm mesh glass fabric net showed a 1.8 time increase (Fig 4). The dependency of reinforced foam cement concrete flexural strength on material thickness and samples size were also investigated. Compressive strength measurement experiments showed that standard prisms (40×40×160 mm) ruptured regardless whether they were reinforced with carbon fibres or additionally by a glass fabric net (Fig 5, samples 1, 2). Thin-wall specimens under load bent at first, later ruptured, however the net was not destroyed. A gypsum board was also tested for comparison. The obtained data is given in Fig 5. Thin-wall (10 mm) specimens under a load bent and returned to initial position when the load was removed during testing. The boards behaved springly, but did not rupture. It was found that thin-wall foam cement shock-resistance does not depend on the article thickness. It was compared with “Bison” firm boards. The obtained results are given in Fie 6. As we can see, reinforced foam cement concrete specimen shock-resistance reaches a (7,0 ÷ 8,0) · 10−3 MPa · m value, while specimens without a reinforcing net give a shock-resistance value of only 1,35 · 10−3 MPa · m, which is substantially lower than for control samples. It is well known, that steaming increases the cement concrete flexural strength [10] and the steaming duration depends on its temperature [11]. It was determined, that with the aim of ensuring the glass fibre surface polymer layer stability, the steaming should be conducted at 45–50 °C temperature. In this case, its flexural strength increases by 2,6 times (Fig 7a, sample 3) in comparison with the interval of temperatures 55–85 °C. The steamed and hardened in natural conditions foam cement concrete microstructure is similar. This was confirmed by X-raygrams and thermograms (Fig 8 and 9). So we came to the conclusion, that clinker mineral hydratation takes place during the hardening of foam cement concrete and tobermorite groups calcium hydrosilicates are formed. The main conclusion: we can increase the flexural strength up to 2 times and the shock-resistance by 5.5 times by reinforcing non-autoclave foam cement concrete with a glass fibre. Article in Lithuanian. First Published Online: 26 Jul 2012